DETERMINATION OF ACUTE MERCURY TOXICITY TO DEVELOPING STAGES OF CYPRINUS CARPIO AND CIRRHINUS MRIGALA - SHRIVASTAVA, SHARD; RAO, K S; DHANEKAR, S; PANDYA, S S (Fishery Technology, 2017)
Toxicity of inorganic mercury to different life history stages of fresh water fishes, Cyprinus carpio and Cirrhinus mrigala were demonstrated by static bioassays. 48 and 94 % of egg hatching occurred in controls at 72 and 24 h of experimentation in C. carpio and C. mrigala respectively. While fish eggs in water containing mercuric chloride showed delayed development as compared to the control. LC50, LC100 and safe concentrations of hatchling, fry and :fingerling were calculated. Hatchling and fry wereobserved to be more susceptible as compared to fingerlings of C. carpio and C. mrigala.